2015
DOI: 10.1186/s12888-015-0462-5
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes of acceptability and lack of condemnation toward suicide may be predictive of post-discharge suicide attempts

Abstract: BackgroundSuicide attempts (SA) after psychiatric hospitalization continue to be a major cause of morbidity. Implicit measures may enhance our ability to assess suicide risk. In this context, we describe the first use of the Suicide Opinion Questionnaire (SOQ) to identify post-discharge suicide attempters.MethodsAdult psychiatric inpatients admitted for suicidality (N = 91) were administered a battery of measures including the SOQ, and forty were reached and reassessed for SA at two months post-discharge. Expl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 54 publications
1
11
0
Order By: Relevance
“…Suicide acceptability which can be seen as one kind of cognition about suicide should also be associated with suicide attempt. This possible association was also discussed in a previous study (Galynker et al, 2015).…”
Section: Discussionsupporting
confidence: 75%
“…Suicide acceptability which can be seen as one kind of cognition about suicide should also be associated with suicide attempt. This possible association was also discussed in a previous study (Galynker et al, 2015).…”
Section: Discussionsupporting
confidence: 75%
“…Nineteen studies evaluated the accuracy of methods to identify suicide risk (28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46) [see table in online supplement]. No studies described the adverse effects of risk assessment methods.…”
Section: Methods To Identify Suicide Riskmentioning
confidence: 99%
“…No studies described the adverse effects of risk assessment methods. Five studies evaluated methods that could be offered to general populations (universal or primary prevention) (32,36,37,39,42); nine studies evaluated methods that target subpopulations likely to be at increased risk of suicide, such as patients presenting to emergency departments (selective or secondary prevention) (28)(29)(30)33,34,38,40,41,46); and five studies evaluated methods for individuals who have already been identified as having increased risk, such as patients admitted to a hospital for suicidal ideation (tertiary prevention) (31,35,(43)(44)(45). Studies enrolled participants from the community, online, emergency departments, and psychiatry services or used data from existing patient medical records or administrative databases.…”
Section: Methods To Identify Suicide Riskmentioning
confidence: 99%
See 1 more Smart Citation
“…The negative consequences of suicide cannot be understated in terms of potential years of life lost, substantial medical and work loss costs, and devastating emotional and financial costs to family and friends (Brent, ; Centers for Disease Control and Prevention, ). Attitudes toward suicide, which appear to be a good indicator of suicidal behavior (Galynker et al., ; Phillips and Luth, ), may have shifted in recent decades, as reflected in the passage of legalized physician‐assisted suicide (PAS) in six states since 1999 (Brown, ). The legalization of a previously prohibited practice may reflect evolving attitudes toward suicide, at least in the case of an incurable disease.…”
mentioning
confidence: 99%